Rising food prices: What should be done? - von Braun, Joachim (Wiley, 2008)
Rising Food Prices: What Should Be Done?The sharp increase in world food prices has raised serious concerns about the food and nutrition situation of poor people in developing countries, about inflation, and about civil unrest in some countries. This article briefly examines the causes of these price increases, the consequences especially for the world’s poorest households and the policy responses so far in the developing world. It argues that facing the new challenges to world agriculture requires a set of sound short‐ and longer‐term policy actions in three main areas. Firstly, developing‐country governments should expand social protection programs, and aid donors should increase food‐related development aid, where needed. Secondly, investment in agriculture, particularly in agricultural science and technology and for improved market access of small farmers, at a national and global scale, to address the long‐term problem of boosting supply. Thirdly, agriculture trade and energy policy reforms, in which developed countries would revise their grain‐based biofuel policies and agricultural trade policies; and developing countries would stop the new trade‐distorting policies with which they are damaging each other. In the face of rising food prices, both developing and developed countries have a role to play in creating a world where all people have enough food for a healthy and productive life.